Salivary cortisol concentration in fattening heifers kept in an enriched environment at different stocking densities - Matković, Kristina (Array, 2021)
The aim of the study was to assess the effect of environmental enrichment and different stocking densities on the level of stress in the fattening cattle by measuring salivary cortisol concentration. A total of 320 saliva samples obtained from heifers during the final four-month fattening period was analyzed by a colorimetric competitive enzyme immunoassay. The heifers were housed at 3.3 and 4.5 m2/animal in standard production conditions that were additionally enriched with a mechanical grooming brush and salt blocks in experimental groups. The study results have demonstrated that a cortisol concentration at the end of fattening was significantly higher, as compared with the initial levels in all heifer groups, without significant intergroup differences. There was no significant correlation between the usage of a grooming brush and cortisol concentration, whereas a significant negative correlation was detected between the salt block usage and cortisol concentration, suggesting a beneficial effect of this simple, commercially available and relatively inexpensive environmental enrichment.